Students’ English Learning Strategies Assisted with e-Resources in Blended Learning - Maghfiroh, Ana; Unaiziah, Elfina Anggi Nafisatul; Mustikawati, Diyah Atiek; Susilowati, Tintin (Universitas Pendidikan Mandalika, 2024)
Blended learning yields some challenges and difficulties for learners, and they should have an appropriate strategy to deal with the use of e-resources. This research aimed at: (1) explaining the various learning strategies used by students to learn English using e-resources in blended learning, and (2) determining the factors that influence their choice of these strategies. The researcher used descriptive-quantitative methods in this study, with the participants involving 2 universities. The SILL questionnaire and interviews were used to collect the data. The results showed that the participants mostly used the metacognitive method, with an average of 3.86. The study also revealed that students used five other methods, including cognitive (M = 3.35), compensation (M = 3.34), affective (M = 3.20), social (M = 3.16), and memory (M = 3.14). Moreover, students’ use of these strategies was influenced by some factors, including motivation to learn English, learning style, and ease of learning. In conclusion, the various strategies employed for learning English were different, as were the factors influencing strategy selection by each participant. This research provides meaningful insights into how the blended learning can be boosted through the implementation of appropriate learning strategies, particularly related to the use of e-resources, so that it will increase students' comprehension and achievement during the learning process.